"Ours is the Strangest Situation, Ours is Different from Most Peoples": Spousal Caregiver Perspectives on the Complex Challenges of Dementia Caregiving in Late-Life Marriage. Issue 6 (18th August 2019) - Roberts, Emily; Struckmeyer, Kristopher M.
Abstract: The relationship between the person with dementia with family caregivers is a key factor in maintaining a sense of self and personhood. Spousal caregiving in particular can create a world of shared meaning, and in the context of the presence of cognitive decline in one spouse, couple hood is essential to a full understanding of how spouses live with and respond to the impact of dementia. While much research has focused on the strengths of long-term married couples caring for a spouse with dementia, there is currently little research on how dementia impacts couples in late-life marriage. This qualitative case study focusses on two female caregivers in late-life marriages negotiating the challenges of caregiving for a spouse with dementia. Spouse 1 returned to live with her ex-husband in order to care for him through his dementia journey and they recently remarried. Spouse 2 married a close friend of the family prior to his dementia diagnosis. While participant shared perspectives include: (1) family dynamics, (2) isolation, (3) financial concerns, and (4) acceptance of their role in their spouse's dementia journey, their long-term outlooks are divergent due to the complexity of their motives for entering in to late-life marriage.